Determinación de la calidad de agua del sistema de riego Guangopud Gatazo provincia de Chimborazo - García García, Maritza Yolanda (2024)
The agricultural sector in Ecuador is of utmost importance; it provides a source of income to many families; this action requires an irrigation system that supplies the necessary humidity to the crops, and the products are not affected. Therefore, irrigation water quality provides profitable production and harvests of considerable volume, which is why this research was carried out. It aims to determine the quality of the water of the Guangopud Gatazo irrigation system. For this, within the irrigation system, eight sampling points were determined, in which studies were carried out on the physical-chemical and microbiological parameters such as temperature, pH, total dissolved solids, sulfates, chlorides, carbonates, bicarbonates, nitrates, calcium, sodium, magnesium and potassium, in addition, the indices of the Sodium Adsorption Ratio (RAS) and Residual Sodium Carbonate (RSC) were calculated, in the period March-May 2023. The values of the mentioned parameters are within the permissible limits of the MAATE and the FAO, except chlorides that exceed the allowable limits; however, based on the results obtained from the calculations of the different quality indices, they were classified as waters of good to excellent quality, that is to say, they are suitable for agricultural irrigation. In addition, conservation and mitigation measures that could be implemented to preserve the quality of the water in the irrigation system were proposed.